Continuous flow synthesis of 6-monoamino-6-monodeoxy-β-cyclodextrin - Orosz, János Máté; Ujj, Dóra; Kasal, Petr; Benkovics, Gábor; Bálint, Erika (Beilstein Journal of Organic Chemistry, 2023)
The first continuous flow method was developed for the synthesis of 6-monoamino-6-monodeoxy-β-cyclodextrin starting from native β-cyclodextrin through three reaction steps, such as monotosylation, azidation and reduction. All reaction steps were studied separately and optimized under continuous flow conditions. After the optimization, the reaction steps were coupled in a semi-continuous flow system, since a solvent exchange had to be performed after the tosylation. However, the azidation and the reduction steps were compatible to be coupled in one flow system obtaining 6-monoamino-6-monodeoxy-β-cyclodextrin in a high yield. Our flow method developed is safer and faster than the batch approaches.
Keywords: azidation; continuous flow; β-cyclodextrin; H-cube; 6-monoamino-6-monodeoxy-β-cyclodextrin; monosubstitution; reduction

(untitled) - Szejtli, J. (Chem. Rev., 1998)

Ger. Patent - Freudenberg, K.; Cramer, F.; Plieninger, H. (Process for the preparation of inclusion compounds of physiologically active organic compounds, 1953)

(untitled) - Crini, G. (Chem. Rev., 2014)

(untitled) - Cornwell, M. J.; Huff, J. B.; Bieniarz, C. (Tetrahedron Lett., 1995)

(untitled) - Kasal, P.; Jindřich, J. (Molecules, 2021)

(untitled) - Melton, L. D.; Slessor, K. N. (Carbohydr. Res., 1971)

(untitled) - Matsui, Y.; Yokoi, T.; Mochida, K. (Chem. Lett., 1976)

(untitled) - Petter, R. C.; Salek, J. S.; Sikorski, C. T.; Kumaravel, G.; Lin, F.-T. (J. Am. Chem. Soc., 1990)

(untitled) - Djedaïni-Pilard, F.; Azaroual-Bellanger, N.; Gosnat, M.; Vernet, D.; Perly, B. (J. Chem. Soc., Perkin Trans. 2, 1995)

(untitled) - Uekama, K.; Minami, K.; Hirayama, F. (J. Med. Chem., 1997)

(untitled) - Kahee, F.; Tsutomu, T.; Taiji, I.; Toshitaka, K. (Chem. Lett., 1988)

(untitled) - Palin, R.; Grove, S. J. A.; Prosser, A. B.; Zhang, M.-Q. (Tetrahedron Lett., 2001)

(untitled) - Fujita, K.; Yamamura, H.; Imoto, T.; Tabushi, I. (Chem. Lett., 1988)

(untitled) - Jicsinszky, L.; Iványi, R. (Carbohydr. Polym., 2001)

(untitled) - Ueno, A.; Moriwaki, F.; Osa, T.; Hamada, F.; Murai, K. (Tetrahedron, 1987)

(untitled) - Bednářová, E.; Hybelbauerová, S.; Jindřich, J. (Beilstein J. Org. Chem., 2016)

(untitled) - Fikes, L. E.; Winn, D. T.; Sweger, R. W.; Johnson, M. P.; Czarnik, A. W. (J. Am. Chem. Soc., 1992)

(untitled) - Popr, M.; Hybelbauerová, S.; Jindřich, J. (Beilstein J. Org. Chem., 2014)

(untitled) - Martin, K. A.; Czarnik, A. W. (Tetrahedron Lett., 1994)

(untitled) - Yoon, J.; Hong, S.; Martin, K. A.; Czarnik, A. W. (J. Org. Chem., 1995)

(untitled) - Martina, K.; Trotta, F.; Robaldo, B.; Belliardi, N.; Jicsinszky, L.; Cravotto, G. (Tetrahedron Lett., 2007)

(untitled) - Menuel, S.; Saitzek, S.; Monflier, E.; Hapiot, F. (Beilstein J. Org. Chem., 2020)

(untitled) - Menuel, S.; Doumert, B.; Saitzek, S.; Ponchel, A.; Delevoye, L.; Monflier, E.; Hapiot, F. (J. Org. Chem., 2015)

(untitled) - Cravotto, G.; Caporaso, M.; Jicsinszky, L.; Martina, K. (Beilstein J. Org. Chem., 2016)

(untitled) - Jicsinszky, L.; Rossi, F.; Solarino, R.; Cravotto, G. (Molecules, 2023)

Ullmann’s Encyclopedia of Industrial Chemistry (Wiley-VCH, 2000)

(untitled) - Plutschack, M. B.; Pieber, B.; Gilmore, K.; Seeberger, P. H. (Chem. Rev., 2017)

(untitled) - Hacket, F.; Simova, S.; Schneider, H.-J. (J. Phys. Org. Chem., 2001)

(untitled) - Defaye, J.; Gadelle, A.; Guiller, A.; Darcy, R.; O'Sullivan, T. (Carbohydr. Res., 1989)

(untitled) - Byun, H.-S.; Zhong, N.; Bittman, R. (Org. Synth., 2000)

(untitled) - Trotta, F.; Martina, K.; Robaldo, B.; Barge, A.; Cravotto, G. (J. Inclusion Phenom. Macrocyclic Chem., 2007)

(untitled) - Zhong, N.; Byun, H.-S.; Bittman, R. (Tetrahedron Lett., 1998)

(untitled) - McNaughton, M.; Engman, L.; Birmingham, A.; Powis, G.; Cotgreave, I. A. (J. Med. Chem., 2004)

(untitled) - Tripodo, G.; Wischke, C.; Neffe, A. T.; Lendlein, A. (Carbohydr. Res., 2013)

(untitled) - Vizitiu, D.; Walkinshaw, C. S.; Gorin, B. I.; Thatcher, G. R. J. (J. Org. Chem., 1997)

(untitled) - Ekberg, B.; Andersson, L. I.; Mosbach, K. (Carbohydr. Res., 1989)

(untitled) - Sforza, S.; Galaverna, G.; Corradini, R.; Dossena, A.; Marchelli, R. (J. Am. Soc. Mass Spectrom., 2003)

(untitled) - Brady, B.; Lynam, N.; O'Sullivan, T.; Ahern, C.; Darcy, R. (Org. Synth., 2000)

(untitled) - Xu, M.; Wu, S.; Zeng, F.; Yu, C. (Langmuir, 2010)

(untitled) - Uchida, W.; Yoshikawa, M.; Seki, T.; Miki, R.; Seki, T.; Fujihara, T.; Ishimaru, Y.; Egawa, Y. (J. Inclusion Phenom. Macrocyclic Chem., 2017)

(untitled) - Quan, C.-Y.; Chen, J.-X.; Wang, H.-Y.; Li, C.; Chang, C.; Zhang, X.-Z.; Zhuo, R.-X. (ACS Nano, 2010)

(untitled) - Chwalek, M.; Auzély, R.; Fort, S. (Org. Biomol. Chem., 2009)

(untitled) - Yang, F.; Zhang, Y.; Guo, H. (New J. Chem., 2013)

(untitled) - Xu, W.; Liang, W.; Wu, W.; Fan, C.; Rao, M.; Su, D.; Zhong, Z.; Yang, C. (Chem. – Eur. J., 2018)

(untitled) - Brown, S. E.; Coates, J. H.; Coghlan, D. R.; Easton, C. J.; Vaneyk, S. J.; Janowski, W.; Lepore, A.; Lincoln, S. F.; Luo, Y.; May, B. L.; Schiesser, D. S.; Wang, P.; et al. (Aust. J. Chem., 1993)

(untitled) - Bonnet, V.; Duval, R.; Tran, V.; Rabiller, C. (Eur. J. Org. Chem., 2003)

(untitled) - Jones, R. V.; Godorhazy, L.; Varga, N.; Szalay, D.; Urge, L.; Darvas, F. (J. Comb. Chem., 2006)

(untitled) - Reddy, L. R.; Reddy, M. A.; Bhanumathi, N.; Rao, K. R. (Indian J. Chem., Sect. B, 2002)